(untitled) (Bangladesh Journal of Medical Education, 2021)
Over last few months, educational institutes across the globe have been forced to close the campuses and switch to virtual classes. Learning is a hard job and studying online can make someone feel isolated, confused or discouraged without proper guidance. The current paper presents the results of a questionnaire-based cross-sectional study conducted in November 2020 on teachers of Chattagram International Medical College, a non-government medical college in Bangladesh. Altogether 52 teachers of CIMC participated in the study, which corresponded to 85% response rate. More than 90% teachers preferred screen-share during the class, half of the teachers considered internet connectivity as most challenging issue in taking class. Remarkable findings in closed questionnaire reflected interest among the faculty for online class, well-maintained discipline in the class, appropriate topic selection, satisfactory ownership of device for online class, non-preference of online class as a good substitute of face-to-face class and partial preference to keep virtual background as an option for teaching even after resuming face-to-face class. Key recommendations from the study included institutional support regarding internet connectivity and logistics, effective interaction with the students to make the classes more meaningful as well as proper training to the teachers to enhance proficiency in online classes. Finally, virtual class can never totally replace face-to-face class; however, this intelligent skill can be kept as an option for teaching in selective circumstances even after pandemic is over and face-to-face classes have been resumed. Bangladesh Journal of Medical Education Vol.12(1) 2021: 3-9